A review on health benefits and processing of tempeh with outlines on its functional microbes - Teoh, Sze Qi; Chin, Nyuk Ling; Chong, Chun Wie; Mat Ripen, Adiratna; How, Syahmeer; Lim, Joyce Jen Li (Elsevier B.V., 2024)
Tempeh is a nutritious fermented legume food made from soybeans and commonly consumed in Southeast Asia especially in Indonesia and Malaysia. The fermentation process involves growth of mold, Rhizopus spp. which transforms soybeans into a white firm cake-like product as enzymes break down complex nutrients in soybeans into simpler forms making the high protein and nutrient rich food more bioavailable. Soybeans fermentation also leads to the production of metabolites such as organic acids, antioxidants and antimicrobial compounds which increase the vitamins content, enhance the nutritional value and shelf life of tempeh. Consumption of tempeh has been linked to various health advantages including antidiabetic effects, cholesterol-lowering properties, improved cognitive function, antitumor and anticancer properties, anti-aging effects and improved gut health as well as reduced risk of cardiovascular disease. This paper summarises useful information on tempeh which includes health benefits, nutrition and functional microbes isolated. It includes information on processing and substrates to provide more avenues to novel and sustainable food product development as tempeh offers an excellent alternative to plant-based protein source.